ANALYZING THE EFFECT OF LEADERSHIP STYLE AND JOB ENVIRONMENT TOWARDS EMPLOYEE TURNOVER INTENTION (CASE STUDY : PT.MEARES SOPUTAN MINING/PT.TAMBANG TONDANO NUSAJAYA) - Tangkudung, Yulita (Jurnal Berkala Ilmiah Efisiensi, 2015)
ABSTRACT A job is an activity, and often performed in exchange for payment. A person usually begins a job by becoming an employee, volunteering, or starting a business. Quite often we see people who move jobs from one profession to another profession. There were also several factors that cause employees out or moved out of a job or profession with different reasons. This study aims to analyzing leadership style and job environment towards employee turnover intention. 45 employees of PT.Meares Soputan Mining/PT.Tambang Tondano Nusajaya were surveyed as respondents. The finding shows that leadership style and job environment have significant influence on employee turnover intention simultaneously. While partially, only job environment has significant influence on employee turnover intention, whereas leadership style does not have any significant influence on employee turnover intention. Creating the good environment is very important to reducing the turnover intention of the employees. Keywords : Leadership style, job environment, employee turnover intention